Towards Standardized Conformance Test Suite for ISO Transport Layer Protocol - El-Gendy, Hazem Mostafa; Talkhan, Ihab ElSayed (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, we develop a sound Conformance Test Suite for the Transport Layer Protocol Internationally standardized by both ISO and IEC. This is to test the implementations of the protocol, promote and facilitate standardized test suites, and promote the use of formal methods. We use formal methods for the generation of testing sequences to make the results sound. The protocol is formally specified in Lotos; the ISO/IEC Formal Description Technique for computer/communications protocols and distributed systems.